The Effect of Servant Leadership and Organizational Commitment on Organizational Citizenship Behavior: Job Satisfaction as Mediating Variable - Wilia Roza; Robby Dharma; Bayu Pratama Azka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
The Effect of Servant Leadership and Organizational Commitment on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable at PT. Karya Semangat Mandiri Padang. This study aims to examine how much influence Servant Leadership and Organizational Commitment to Job Satisfaction and how much influence Servant Leadership, Organizational Commitment and Organizational Citizenship Behavior (OCB) on Job Satisfaction. Methods of data collection through surveys and distributing questionnaires, with a sample of 85 respondents obtained by the Slovin formula in the employee population of PT. Karya Semangat Mandiri Padang. The analysis method used is correlation analysis, multiple linear regression and path analysis using SPSS 16. The results obtained based on the T test (partial test) obtained Servant Leadership and Organizational Commitment parisally have a significant effect on the Organizational Citizenship Behavior (OCB) of PT. Karya Semangat Mandiri. Based on the F test (Simultaneous), it was found that Servant Leadership and Organizational Commitment parisally had a significant effect on job satisfaction of employees of PT. Karya Semangat Mandiri.